2017
DOI: 10.1002/2016ja022666
|View full text |Cite
|
Sign up to set email alerts
|

Shock aurora: Field‐aligned discrete structures moving along the dawnside oval

Abstract: Generated by interplanetary shocks or solar wind pressure pulses, shock aurora has transient, global, and dynamic significances and provides a direct manifestation of the solar wind‐magnetosphere‐ionosphere interaction. As a part of a series of studies of the shock aurora, this paper focuses on the interaction at the morning magnetopause and its auroral manifestation at ~06 magnetic local time, where the velocity and magnetic field shears dominate the interaction. Flow shears can generate wave‐like structures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 77 publications
3
12
0
Order By: Relevance
“…A very typical example is the shock aurora that is generated by interplanetary shocks or pressure pulses on the dayside and followed by a global response in the auroral and magnetospheric dynamics and even in the dayside low‐latitude ionosphere. The shock aurora was revealed by the UV auroral imaging from spacecraft, including DE1, Polar, and IMAGE (e.g., Craven et al, 1986; Meurant et al, 2004; Spann et al, 1998; Zhou & Tsurutani, 1999) and was corroborated via analyzing observations from FAST, DMSP, GPS satellites, and the ground‐based observations including Super Dual Auroral Radar Network (SuperDARN), ASI, and Meridian Scanning Photometer (MSP) (e.g., Holmes et al, 2014; Jin et al, 2016; Zhou et al, 2003, 2009, 2010, 2017).…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…A very typical example is the shock aurora that is generated by interplanetary shocks or pressure pulses on the dayside and followed by a global response in the auroral and magnetospheric dynamics and even in the dayside low‐latitude ionosphere. The shock aurora was revealed by the UV auroral imaging from spacecraft, including DE1, Polar, and IMAGE (e.g., Craven et al, 1986; Meurant et al, 2004; Spann et al, 1998; Zhou & Tsurutani, 1999) and was corroborated via analyzing observations from FAST, DMSP, GPS satellites, and the ground‐based observations including Super Dual Auroral Radar Network (SuperDARN), ASI, and Meridian Scanning Photometer (MSP) (e.g., Holmes et al, 2014; Jin et al, 2016; Zhou et al, 2003, 2009, 2010, 2017).…”
Section: Introductionmentioning
confidence: 85%
“…Ample studies have shown that dayside diffuse and discrete aurorae (from~60°to 80°MLat) are direct and reliable indicators of solar wind transients in the ionosphere. These indicators include the shock aurora caused by interplanetary shocks (e.g., Zhou et al, 2009;Zhou, Haerendel, et al, 2017;Zhou & Tsurutani, 1999), dayside auroral spots caused by solar wind pressure pulses (e.g., Hubert et al, 2003;Zhang et al, 2002), the throat aurora generated by the magnetospheric cold plasma flowing into the magnetopause reconnection site (e.g., Han et al, 2016), the locally enhanced aurora related to magnetopause hot flow anomalies (e.g., Fillingim et al, 2011; Sibeck et Comparison between MOD6 and MOD3 for the same viewing geometry. The sky brightness values are compared at two different altitudes (z = 30 km and z = 50 km) for both MOD3 and MOD6, showing an offset in the infrared region of the spectrum between the old MOD3 runs and the new MOD6 runs.…”
Section: New Science Enabled By This Observational Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Consequentially, as NO abundance increases during the precipitating events, the enhancement of the altitudinally integrated NO cooling can be observed as well as in Figures 4e and 4f. The precipitating particles of a few keV at the predawnside and dawnside likely associate with intense field-aligned currents as a result of magnetic and velocity shears in the magnetosphere during shock aurora (Zhou et al, 2017). Overall, the NO cooling enhancement occurs with the particle precipitation.…”
Section: Journal Of Geophysical Research: Space Physicsmentioning
confidence: 96%
“…Red arcs are seen more in and near local noon in the cusp area where the dayside magnetic reconnection dominates [ Moen et al , ; Sandholt et al , , ; Chaston et al , ; Zhou et al , , ]. During the northward interplanetary magnetic field, auroral streaks are seen in the dawnside where the viscous interaction dominates and presumably associated with the Kelvin‐Helmholtz instability along the magnetopause flank [ Zhou et al , ]. During interplanetary shock or solar wind pressure pulse compressions, diffuse aurorae occur and propagate antisunward at a very high ionospheric speed, mirroring the moving compression on the magnetopause that is 10 to 20 Re away from the aurora [ Zhou and Tsurutani , ; Holmes et al , ; Jin et al , ].…”
Section: Scientific Motivationmentioning
confidence: 99%